Strength-shoes review challenged - Hatfield, F. C. (Sportscience)
This article includes copies of correspondence from the manufacturer of Strength Shoes and an abstract in which positive effects of the use of Strength Shoes are reported. Until better evidence is published, I still advise caution in the use of this training aid. Including a study which analyzed the effectiveness of the Strength Shoe in improving sport specific variables. Male athletes ages 18-22 yr of age (n=20) were studied to assess the effects of 9 weeks of training with the Strength Shoe. The manufactures training protocol emphasizing proper warm-up, cool-down and progression was followed. Subjects trained three days per week for approximately 45-60 minutes per session. The subjects were randomly divided into a control group (wearing the Strength Shoe). Analysis of variance (ANOVA) was used to determine significant differences between the control and treatment group (p<.05). Statistical analysis demonstrated a significant improvement the following variables; relative W/kg-1), Vertical displacement (2.01 in v.3.58 in) and 40 yd. speed (-.06 v. 1.14). No significant difference was found in upper and lower leg size, and lower back strength. In addition, this study found no significant difference in the report of injuries between the control and treatment groups. This study, which is experimental by nature is consistent with that of previously reported subjective data. The results of this study strongly suggest that the use of the Strength Shoe is indeed and effective training tool in the development of anaerobic power.